Studies of the linguistic representation of the concept "Distance" - Otakhonova Makhliyo Kamaldinovna (International Journal on Orange Technologies, 2020)
The article presents a brief description of Conceptology as a version of Cognitive linguistic and depicts its main distinctions from Contensive and Cognitive (in narrow sense) linguistics as a form of expression of Russian mentality in its basic manifestations. The attempt to describe a certain area of ​​vocabulary (spatial adjectives)is based on a distributive and situational analysis of the semantics of the words in question. The peculiarities of the representation of the concept "distance" in the semantics of the studied adjectives were identified, according to which adjectives were divided into subgroups, such as for the group high , tall , lofty , low - this is a common complex sign of designating a relatively large / small vertical size of "vertically located (standing) objects, counted up from the support plane located below, however this size should be large enough".